Pemodelan dan Simulasi Mobile Robot - 3 Trailers dengan Kendali PID - Sinuraya, Enda Wista (Departemen Teknik Elektro, Universitas Diponegoro, 2012)
The mobile robot and trailer model presents a classic challenge in the field of control theory. Trailers, on the other hand, have been developed and widely used in the industry. The main focus of industrial design is set on reducing tracking error from a reference trajectory. We develop a design theory of trailer systems with passive steering and the steering wheel’s angle . From simulation result, The mobile robot with proportional controller shows good result in following the required trajectory. Keywords : mobile robot and trailer, trajectory, passive steering, proportional controller